2011
DOI: 10.1177/0731684411399135
|View full text |Cite
|
Sign up to set email alerts
|

Study on dielectric, thermal, and mechanical properties of the ethylene vinyl acetate reinforced with ground tire rubber

Abstract: Mass production of tires, as well as the difficult storage or elimination is a real environmental problem. Various methods for recycling tires are currently used, such as mechanical grinding, which puts vulcanized rubber, steel, and fibers apart. The rubber may be used in several industrial applications such as flooring, insulations, footwear, etc. The aim of this article focuses on finding a new application for the old used tires (GTR). Tire dust and recycled EVA thermoplastic have been mixed, and we have che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
(26 reference statements)
5
20
0
Order By: Relevance
“…Colom et al [35] observed the drop in tensile strength of 20 wt% GTR containing HDPE blend with <200 µm particle size was only 25% whereas when bigger particle size (>500 µm) was used the drop observed was 51%. Similar observation was also noted by Mujal-Rosas et al [88] in their work with EVA/GTR where they used three different particle sizes (<200, 200 -500, >500 µm).…”
Section: Thermoplastic Blendssupporting
confidence: 79%
See 3 more Smart Citations
“…Colom et al [35] observed the drop in tensile strength of 20 wt% GTR containing HDPE blend with <200 µm particle size was only 25% whereas when bigger particle size (>500 µm) was used the drop observed was 51%. Similar observation was also noted by Mujal-Rosas et al [88] in their work with EVA/GTR where they used three different particle sizes (<200, 200 -500, >500 µm).…”
Section: Thermoplastic Blendssupporting
confidence: 79%
“…Sonnier et al [34] reported loading and particle size of GTR had no significance on melting temperature and crystallinity index of the LDPE/GTR blends. Mujal-Rosas et al [88] in their work with different particle size of GTR disperse in EVA phase concluded the GTR particle size or loading has no significant influence on the matrix in terms of crystallinity due to little interaction between GTR and EVA. The crystallinity of blends with <200 µm particle size was equivalent to blend with >500 µm particle size has further enhanced the claim.…”
Section: Calorimetric Evaluationmentioning
confidence: 97%
See 2 more Smart Citations
“…Colom et al (2009) observed the drop in tensile strength of 20 wt% GTR containing HDPE blend with <200 µm particle size was only 25% whereas when bigger particle size (>500 µm) was used the drop observed was 51%. Similar observation was also noted by Mujal-Rosas et al (2011) in their work with EVA/GTR where they used three different particle sizes (<200, 200 -500, >500 µm). Sonnier et al (2007) used three different GTR particle sizes which were all >500 µm and did not observe significant influence of particle size on the mechanical properties of 50 wt% GTR loaded LDPE blend.…”
Section: Influence Of Particle Sizesupporting
confidence: 63%